Management of The Dampier Strait Regional Water Conservation Area in Raja Ampat Regency - F.X Adi Saputra; Fredinan Yulianda; Taryono Taryono; Riana Faiza (Faculty of Fisheries and Marine Science, Brawijaya University, 2023)
The establishment of conservation areas is a form of conservation and utilization of coastal areas and small islands and their ecosystems in an integrated manner to ensure the existence and sustainability of their resources. This study aims to analyze the implementation of the management of the Dampier Strait water conservation area using the Analytical Network Process (ANP) method. Four important aspects to describe the problems and solutions in this study are sourced from ecological, economic, social, and institutional clusters and sub-clusters. The results of the analysis show that the priority problem of managing the water conservation area in the Dampier Strait area originates from the ecological cluster. The results of the sub-cluster analysis show priority problems, namely: (1) Ecosystem degradation with a value of 0.4529, (2) Community welfare is still low with a value of 0.4361 based on economic aspects, (3) Fishing that is not environmentally friendly with a value of 0 .4089 based on social aspects, and (4) Regulations that have not run optimally from the institutional aspect with a value of 0.3844. Referring to the priority problems in each sub-cluster, the following priority solutions were obtained, namely: (1) Coordinating with a score of 0.5447 from the social aspect, (2) Forming a partnership network with a value of 0.5438 from the institutional aspect, (3) Increased community capacity 0.4351, and (4) Improved ecosystem function with a value of 0.4147 from the ecological aspect.